Acceptance of Acute Kidney Injury Alert by Providers in Cardiac Surgery Intensive Care Unit - Nevin, Connor; Shawwa, Khaled; Pincavitch, Jami; Neely, Rebecca L.; Goodwin, Donnie; McCarthy, Paul; Mohamed, Nada; Mullett, Charles; Smith, Gordon S.; Kellum, John A.; Sakhuja, Ankit (Applied Clinical Informatics, 2023)
Background Acute kidney injury (AKI) is a common complication after cardiac surgery and is associated with worse outcomes. Its management relies on early diagnosis, and therefore, electronic alerts have been used to alert clinicians for development of AKI. Electronic alerts are, however, associated with high rates of alert fatigue.Objectives We designed this study to assess the acceptance of user-centered electronic AKI alert by clinicians.Methods We developed a user-centered electronic AKI alert that alerted clinicians of development of AKI in a persistent yet noninterruptive fashion. As the goal of the alert was to alert toward new or worsening AKI, it disappeared 48 hours after being activated. We assessed the acceptance of the alert using surveys at 6 and 12 months after the alert went live.Results At 6 months after their implementation, 38.9% providers reported that they would not have recognized AKI as early as they did without this alert. This number increased to 66.7% by 12 months of survey. Most providers also shared that they re-dosed or discontinued medications earlier, provided earlier management of volume status, avoided intravenous contrast use, and evaluated patients by using point-of-care ultrasounds more due to the alert. Overall, 83.3% respondents reported satisfaction with the electronic AKI alerts at 6 months and 94.4% at 12 months.Conclusion This study showed high rates of acceptance of a user-centered electronic AKI alert over time by clinicians taking care of patients with AKI.
Keywords: alert; clinical decision support; alert fatigue; electronic health record; user-centered alert